How to Supply Assembly Liines - Kopecek, Pavel; Pinte, Milan (Communications - Scientific Letters of the University of Zilina, 2015)
Great efforts are currently dedicated to cost engineering in industry. The lean production approach is a good way to lower production costs. Material flows and treatment should be planned and controlled neither too early nor too late, because early production leads to an increase of stocks of materials and late production to a backlog of orders. This task is especially important in serial production, e.g. in the automotive industry. A buffer stock could be connected with assembly lines in many ways, such as handcarts, fork lift trucks or special cableways. A modern method of material supply in an assembly workshop is the usage of tow trains consisting of a tow truck and several carts. The number of carts in a train can change but it cannot be high because of turnings and crossings. The task is to find and optimize transport routes. This task is considered to be NP-hard. The paper describes several approaches to solving the task.
Keywords: material supplies; heuristic optimization; assembly lines; milk run VRP problem